2002
DOI: 10.1038/sj.bjc.6600111
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of apoptotic regulators CASP9 and DFFA at 1P36.2, reveal rare allele variants in human neuroblastoma tumours

Abstract: The genes encoding Caspase-9 and DFF45 have both recently been mapped to chromosome region 1p36.2, that is a region alleged to involve one or several tumour suppressor genes in neuroblastoma tumours. This study presents an update contig of the 'Smallest Region of Overlap of deletions' in Scandinavian neuroblastoma tumours and suggests that DFF45 is localized in the region. The genomic organization of the human DFF45 gene, deduced by in-silico comparisons of DNA sequences, is described for the first time in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 40 publications
1
36
1
Order By: Relevance
“…The 500 kb deletion partly overlaps the most proximal part of the consensus LOH region determined by us in our set of tumours. We have previously screened all annotated genes within this 500 kb region for mutations in neuroblastoma patients (Ejeskär et al, 2000;Abel et al, 2002;Krona et al, 2003). In this study, we have further explored this genomic region by the characterisation of a predicted gene, APITD1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 500 kb deletion partly overlaps the most proximal part of the consensus LOH region determined by us in our set of tumours. We have previously screened all annotated genes within this 500 kb region for mutations in neuroblastoma patients (Ejeskär et al, 2000;Abel et al, 2002;Krona et al, 2003). In this study, we have further explored this genomic region by the characterisation of a predicted gene, APITD1.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence for the localisation of a neuroblastoma tumour suppressor gene to this region came from the finding of a 500 kb homozygous deletion within our SRO in a neuroblastoma cell line (Ohira et al, 2000). Mutation analysis of the coding sequences of all known genes within this 500 kb region indicated a low frequency of amino-acid changes, implying the presence of yet unidentified genes in the region which might be involved in the development and/or progression of neuroblastoma tumours (Ejeskär et al, 2000;Abel et al, 2002;Krona et al, 2003).…”
mentioning
confidence: 99%
“…However, these studies have not identified a consistent region of deletion. Furthermore, these and other studies have proposed over 20 genes within these regions as candidate neuroblastoma tumor suppressors, none of which have yet been proven to play a significant causative role in neuroblastoma tumor development (Ejeskar et al, 2000;Judson et al, 2000;De Toledo et al, 2001;Huang et al, 2001;Abel et al, 2002;Cerignoli et al, 2002;Krona et al, 2003;Thompson et al, 2003;Mathysen et al, 2004). Our current work was designed to determine the location and extent of 1p deletion in a very large primary tumor cohort by extensive genotyping, sequencing, gene identification, and transcript characterization.…”
Section: Discussionmentioning
confidence: 99%
“…As an overlapping homozygous 500 kb deletion of 1p36.2 -3 was found in an NB cell line (Ohira et al, 2000), the region has been analysed in further detail. In our study of the genes within this region, all seven were screened for mutations and a few were indeed discovered (Ejeskär et al, 2000;Abel et al, 2002Abel et al, , 2004Krona et al, 2003Krona et al, , 2004. We have also explored the expression and methylation status of these genes.…”
mentioning
confidence: 99%